Analysis of Hadith on Taking the Rights of Others in the Phenomenon of Abuse of Authority in the Modern Era: A Study of Takhrij and Syarah Hadith - Nurul Arifin, Wildan (Journal of Takhrij Al-Hadith, 2025)
This study aims to discuss hadiths about taking the rights of others in the context of abuse of authority in the modern era. This study employs a qualitative approach using a descriptive analytical method. The formal object of this study is hadith science, while the material object is the hadith regarding the taking of others' rights as recorded in Imam Muslim's narration No. 3024. The results and discussion of this study indicate that the hadith in question is of the Shahih quality, meeting the criteria of being acceptable and applicable for Islamic practice. This study concludes that the hadith narrated by Imam Muslim No. 3024 is relevant for use as an enrichment of knowledge in the field of the prohibition of taking others' rights.